การเตรียมการด้านที่อยู่อาศัยของผู้สูงอายุที่เป็นสมาชิกกองทุนบำเหน็จบำนาญข้าราชการในกรุงเทพมหานคร - เต็มศิริ ศิริสมบัติ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The rapid emergence of elderly society in Thailand will bring about various problems such as the need for more elderly care and inadequate management of the rights of the elderly. The government pension fund is the public servants longterm saving fund that will ensure that members have savings in case they retire or leave the service. This study aims at analyzing the social, economic and living conditions of government pension fund members in the Bangkok metropolitan area regarding their housing preparation. The study used questionnaires and conducted surveys on 392 samples. The data gathered was analyzed to find housing preparation guidelines for government pension fund members. The study divided governments into 12 categories, and focused on the top 5-namely civil servants, teachers, military officials, unversity employees and police officials which account for 95.86% of the total population. The findings show that 54.86% of the sample group are university graduates and most worked as government officials for 30-39 years; 47.40% earn between 30,000-60,000 baht per month per household, and 36.73% earn 20,000-30,000 baht per month. 61.48% live in a single house anก 76.53% own the property; 50.51% live with their spouse and family. Among these, 43.62% have lived in their present residence for over 20 years. 65.6% have no problems in terms of housing; those having problems are mostly concerned with dilapidated building conditions and insufficient space. Housing preparation data can be divided into 2 groups namely those who do prepare (63.27%) and those who do not prepare for housing (36.73%). The reason for lack of preparation of 76.70% of the latter group is because they already own a property. As for the group the prepares for housing, 34.18% will improve their residence, with 28.90% wanting to renovate only the dilapidated parts. The home improvement budget for 82.09% of the subjects is set between 100,000-500,000 baht. 44.85% say the home improvement budget comes from their savings and 17.60% want to relocate. Most (31.88%) say the reason is to own their own property. In planning for relocation, most (55.07%) want to build their own house; most people in this group (65.79%) already own a plot of land. Most (84.05%) want to build a single house and the majority (31.88%) would prefer to relocate to the suburbs. The top 5 factors influencing their relocation consist of: reasonable price, pleasant environment, safety to life and property, payment conditions, and proximity to family members. As for the relocation budget, most (55.07%) have 1,000,000-2,000,000 baht; 30.81% say the money is from their savings. 11.48% pay for their housing by installments, and 40.00% pay at a rate of 5,001-10,000 baht per month. 31.11% say the property price they are paying off cost between 1,000,000-2,000,000 baht. 51.11% of the property paid by installments are single houses, among these 31.11% are located in the inner Bangkok metropolitan area and 56.25% of the budget comes from loans. All groups express a need for governmental assistance such as the provision of low-inferest funds for the renovation of existing residences (33.16%). Also, they ask that the government ensure a more pleasant environment, etc. The government and agencies concerned should have policies to create awareness about housing preparation before retirement, and provide welfare for appropriate housing that suits the individual s age, occupation and earning so as everyone is capable of owning their own property.